1999
DOI: 10.1116/1.590775
|View full text |Cite
|
Sign up to set email alerts
|

Study of crystal orientation in Cu film on TiN layered structures

Abstract: Articles you may be interested inHighly (002) textured large grain bcc Cr80Mn20 seed layer on Cr50Ti50 amorphous layer for FePt-C granular filmThe influence of the growth rate on the preferred orientation of magnetron-sputtered Ti-Al-N thin films studied by in situ x-ray diffraction J. Appl. Phys. 98, 044901 (2005); 10. 1063/1.1999829 Interfacial mechanism studies of electroless plated Cu films on a -Ta:N layers catalyzed by PIIIThe effect of underlayer texture on Cu film orientation has been studied. Cu te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…The Cu grain growth in the annealed samples can also be noticed. It is reported that Cu diffuses fast in Si and forms Cu-Si compounds at a temperature as low as 200°C and Cu (1 1 1) provides higher electro-migration resistance than that of Cu (2 0 0) [12]. So it can be thought that the Ta-W-N layer effectively suppressed the Cu diffusion into Si.…”
Section: Resultsmentioning
confidence: 97%
“…The Cu grain growth in the annealed samples can also be noticed. It is reported that Cu diffuses fast in Si and forms Cu-Si compounds at a temperature as low as 200°C and Cu (1 1 1) provides higher electro-migration resistance than that of Cu (2 0 0) [12]. So it can be thought that the Ta-W-N layer effectively suppressed the Cu diffusion into Si.…”
Section: Resultsmentioning
confidence: 97%
“…Sharpened (1 1 1) and (2 0 0) peaks of annealed-Cu films indicate the growth of Cu crystalline occurring during annealing, but other crystalline phase like Cu silicide or Zr silicide cannot be observed up to 800°C. On the other hand, it has been reported that Cu (1 1 1) provided higher electro-migration resistance than that of Cu (2 0 0) [12]. In the present experiment, the intensities of Cu (1 1 1) peak are larger than those of Cu (2 0 0) peaks for all specimens (the ratio of the intensities of Cu (1 1 1) to those of Cu (2 0 0) are 35 and 56 for Cu/Zr-Si-N()100 V)/Si and Cu/ Table 1 The sheet resistances of the Cu/Zr-Si-N/Si contacts before and after annealing at 800°C…”
Section: Resultsmentioning
confidence: 94%
“…For instance, it is known that TiN barrier with a strong ͗111͘ orientation enhances Cu͗111͘ texture, which can be a drawback. 9 Behavior of Cu/barrier/Si structures.-In a preliminary report we have shown that Cu/CrC x N y /Si structures were stable under annealing in H 2 ambient until 650°C for 30 min. 17 Above this temperature, two phases crystallize: Cr 3 ͑C 0.8 N 0.2 ͒ 2 and Cr 2 O 3 .…”
Section: Resultsmentioning
confidence: 98%